Упростить выражения :

(m+5)^2 -(m-5)^2

(x+y)^2 -(x-y)^2

(x-6)^2 -9x^2

  • (m+5)^2 -(m-5)^2

    (м+5-м+5)(м+5+м-5)=20м


    (x+y)^2 -(x-y)^2

    (x+y-x+y)(x+y+x-y)=2y*2x=4xy

     

    (x-6)^2 -9x^2

    (x-6-3x)(x-6+3x)=-(6+2x)(2x-6)

  • (m+5)^2 -(m-5)^2 раскрываем по формуле a^2 (+-) 2ab +b^2

    m^2 + 10m +25 - (m^2 - 10m +25)

    m^2 + 10m +25 - m^2 + 10m - 25 cокращаем

    =20m

    ______________________________________________

    (x+y)^2 -(x-y)^2

    x^2 +2xy + y^2 - (x^2 - 2xy + y^2)

    x^2 + 2xy +y^2 - x^2 + 2xy - y^2 сокращаем

    =4xy

    ______________________________________________

    (x-6)^2 -9x^2

    x^2 -12x+36-9x^2=0

    8x^2 +12x-36=0 поделим на 4

    2x^2 + 3ч -9=0

    Через дискриминант корни: x1=1,5, x2= -3

    =2 (x-1,5) (x+3)

    как то так..


See also: